Are people sincere condemning Israeli atrocities? a letter to the world - Hasan, Md. Mahmudul (OnIslam.net, 2014)
Palestine is burning. Israel has been killing innocent men, women and children in hundreds almost every day. People around the world condemn all these atrocities and sympathize with the Palestinians. But are they sincere in their condemnation of the Zionist killers and in their sense of pity for the Palestinians who have been suffering for more than six decades now?